Sputum neutrophils are elevated in smelter workers, and systemic neutrophils are associated with rapid decline in FEV1. Issue 7 (6th April 2016) - Sikkeland, Liv Ingunn Bjoner; Johnsen, Helle Laier; Riste, Tonje Bøyum; Alexis, Neil E; Halvorsen, Bente; Søyseth, Vidar; Kongerud, Johny
Abstract : Objectives: In a previous study on smelter workers we, found significant relationship between exposure to dust and accelerated annual decline in forced expiratory volume in 1 s (FEV1 ). In this cross-sectional study at the end of a follow-up, we aimed to investigate the possible association between annual decline in FEV1 and markers of airways, and systemic inflammation in smelter workers. Methods: Employees (n=76 (27 current smokers)) who had been part of a longitudinal study (9–13 years) that included spirometry (>6 measurements) and respiratory questionnaires, performed induced sputum, exhaled NO and had blood drawn. Participants with annual decline in FEV1 ≥45 mL were compared with participants with annual decline <45 mL; also 26 non-exposed controls were included. Results: Compared with non-exposed controls, smelter workers demonstrated a significantly increased percentage of neutrophils (mean (SD)) (57% (17) vs 31% (15)) and matrix metalloproteinases 8 (MMP-8) levels in sputum, and MMP-9, surfactant protein D (SpD) and transforming growth factor β (TGFb) levels in blood. A significant association in FEV1 ≥45 mL was found for blood neutrophils when controlling for smoking habits (OR=1.7 (95% CI 1.0 to 2.8), p=0.045). Airway and blood protein markers were not associated with annual decline in FEV1 . Conclusions: All workers displayed airway and systemic inflammation characterised by increased levels of neutrophils and MMP-8 in sputum, and MMP-9, SpD and TGFβ in blood compared with non-exposed controls. Blood neutrophils in particular were significantly elevated in those workers with the most rapid decline in lung function. A similar observation was not seen with airway neutrophils. In the present study, we were able to identify systemic but not airway inflammatory markers that can predict increased decline in FEV1 in smelter workers.